Choir transhumance in the Filipino Catholic community in Rome - Facci, Serena; Tuzi, Grazia (European Journal of Musicology, 2022)
The article is part of a research project (2014-2018) among Christian immigrants in Rome and focuses particularly on the Filipino community. Serena Facci presents the general context of the migrant church experience of Rome, a city historically considered as central to the wider transnational community of Catholic Christians, where, thanks to the hosting politics of the Vicariate, there are several ‘national’ and ‘multinational’ churches, characterised by liturgies in different languages and by repertoires of chants in different geocultural styles. The migrants’ position in the holy city is juxtaposed with the multicentricity of the diaspora and the mediation between the motherland and the new places of residence. Grazia Tuzi shows how the Filipinos in Rome represent this multicentricity through the liturgical services of musical groups and choirs from the peripheral churches surrounding Rome. On Sundays, the Filipino micro-communities proceed in a kind of “transhumant” movement according to a predetermined schedule, from their parishes to the Chaplaincy located in the Basilica of Santa Pudenziana, which is the gathering place of all Filipinos living in Rome. Here they accompany the Sunday liturgy and religious Festivals in performances that bear witness to a remarkable musical variety. The analysis of these musical practices and the complex organization of the choir’s "transhumance" from the periphery to the centre can facilitate the understanding of the processes used by this migrant community in the re-articulation and maintenance of their own identity in the new socio-cultural spheres.